Analysis of the mitochondrial maxicircle of Trypanosoma lewisi, a neglected human pathogen. Issue 1 (December 2015) - Lin, Ruo-Hong; Lai, De-Hua; Zheng, Ling-Ling; Wu, Jie; Lukeš, Julius; Hide, Geoff; Lun, Zhao-Rong
Abstract Background The haemoflagellateTrypanosoma lewisi is a kinetoplastid parasite which, as it has been recently reported to cause human disease, deserves increased attention. Characteristic features of all kinetoplastid flagellates are a uniquely structured mitochondrial DNA or kinetoplast, comprised of a network of catenated DNA circles, and RNA editing of mitochondrial transcripts. The aim of this study was to describe the kinetoplast DNA ofT. lewisi . Methods/Results In this study, purified kinetoplast DNA fromT. lewisi was sequenced using high-throughput sequencing in combination with sequencing of PCR amplicons. This allowed the assembly of theT. lewisi kinetoplast maxicircle DNA, which is a homologue of the mitochondrial genome in other eukaryotes. The assembly of 23, 745 bp comprises the non-coding and coding regions. Comparative analysis of the maxicircle sequence ofT. lewisi withTrypanosoma cruzi, Trypanosoma rangeli, Trypanosoma brucei andLeishmania tarentolae revealed that it shares 78 %, 77 %, 74 % and 66 % sequence identity with these parasites, respectively. The high GC content in at least 9 maxicircle genes ofT. lewisi (ATPase6 ; NADH dehydrogenase subunitsND3, ND7, ND8 and ND9 ; G-rich regionsGR3 andGR4 ; cytochrome oxidase subunitCOIII and ribosomal proteinRPS12 ) implies that their products may be extensively edited. A detailed analysis of the non-coding region revealed that it contains numerous repeat motifs and palindromes. Conclusions We have sequenced and comprehensively annotated the kinetoplast maxicircle ofT. lewisi . Our analysis reveals thatT. lewisi is closely related toT. cruzi andT. brucei, and may share similar RNA editing patterns with them rather than withL. tarentolae . These findings provide novel insight into the biological features of this emerging human pathogen.